2018
DOI: 10.1016/j.pulmoe.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COPD patients with early-onset desaturation in the 6-minute walk test

Abstract: Overweight and obesity, as determined by body mass index, seem to behave like markers for early desaturation. This simple anthropometric measure might indicate point to potential early desaturation in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…Desaturation present in 6-minute walk test has been found to be a significant predictor of nocturnal desaturation. This is in concordance with the studies by Garcia-Talavera et al 16 and Moreira et al 17 where 6 minute walk test is found to be an important indicator of nocturnal desaturation and prognosis in COPD. Similar to other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Desaturation present in 6-minute walk test has been found to be a significant predictor of nocturnal desaturation. This is in concordance with the studies by Garcia-Talavera et al 16 and Moreira et al 17 where 6 minute walk test is found to be an important indicator of nocturnal desaturation and prognosis in COPD. Similar to other studies.…”
Section: Discussionsupporting
confidence: 93%
“…The definition of hypoxemia on exercise vary widely. The most used criteria include a nadir arterial oxygen saturation (SpO2) ≤88% [15][16][17][18] and a decrease in SpO2 ≥4% with or without a nadir SpO2<90% [19,23]. In unselected groups of patients with ILD, 49-54% experience exertional hypoxaemia [24,25].…”
Section: Hypoxemia In Ildmentioning
confidence: 99%
“…Oxygen desaturation is believed to be the result of an imbalance between ventilation and perfusion during physical exercise; the chronic limitation of airflow and the lung's elastic recoil ability result in air becoming trapped and a dynamic hyperinflation phenomenon which increases breathing work and oxygen consumption in patients with COPD . In the study by García‐Talavera et al, they observed that both an initial reduced SatO 2 and low DLCO values (defined as SatO 2 ≤ 93% and DLCO ≤ 55%, respectively) were factors associated with early desaturation in the 6MWT (a drop in SatO 2 equal to or greater than 4% in the first minute of the test). However, in said study, obesity (defined as BMI ≥ 30) was the factor most closely related to the presence of early desaturation as well as the repercussions of said event, which was also shown in the ECLIPSE cohort …”
Section: Discussionmentioning
confidence: 99%